FLAMING CELLS DI MULTIPLE MYELOMA - Nursin Abd. Kadir; Hj. Darmawaty E.R,; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2010)
Multiple myeloma is a type of cancer on plasma cells which are system of immune cells in bone marrow that produce antibodies. A47 years old man precented with an excruciatingly painfull bone lytic lesion acompanied with compressive fracture in his Thorakal XIIand first Lumbar vertebral body since a week ago. A complete blood count on admission showed anemia normocytic normocrom withhemoglobin content of 5.3 mg/dL. The blood smear revealed clumping of red blood cells to bound